Building Dignified Teachers: Strategies for Strengthening Manners and Codes of Ethics in Education - Harsa, Gian; Stevani Immelia Putri (Sekolah Tinggi Agama Islam Darul Qur'an Payakumbuh, 2025)
Manners and code of ethics are two fundamental elements that a teacher must have in carrying out his duties and responsibilities as an educator. Manners refer to politeness, noble character, and the ability to put something in its proper place, which reflects the integrity and moral maturity of a teacher. Meanwhile, a code of ethics is a set of rules that regulate professional and moral behavior in the work environment, functioning as a guideline in maintaining the honor and responsibility of the teaching profession. This article examines the meaning, function, and urgency of both in the context of education. It also highlights the importance of teacher manners in the learning process, such as righteous intentions, compassion for students, and the ability to deliver material effectively. In addition, strategies f or strengthening teacher manners and codes of ethics are discussed through a systematic education and training approach, starting from needs analysis, target determination, program preparation, to evaluation. This approach is expected to be able to form teachers who are not only academically competent, but also have strong characters as role models. By strengthening manners and codes of ethics, the world of education will be stronger in realizing a generation that is intelligent, moral, and has integrity.